Aorto-coronary saphenous vein bypass grafting in a patient with a single coronary artery arising from the right aortic sinus. Issue 3 (March 1980) - Milo, S; Kishon, Y; Goor, D; Neufeld, H N
Abstract : A patient who presented with severe angina was found to have an ectopic origin of the entire left coronary system, the left main coronary artery arising from the proximal third of the right coronary artery. Atherosclerotic obstructive lesions were present in the right coronary artery, the left anterior descending artery, and the obtuse marginal branch of the left circumflex coronary artery. The three obstructed vessels were bypassed, using autologous saphenous veins. The patient continues to do well 24 months after his operation. We believe that coronary artery bypass should be carried out in symptomatic patients with abnormal coronary anatomy and atherosclerotic disease.